BLOOD LACTATE LEVELS DURING CONTINUOUS EXERCISE WITH STABLE HEART RATE DETERMINED FROM CONCONI TEST (Fiep Bulletin - online, 2015)
The aim of this study was to verify the blood lactate levels during 45 minutes continuous exercise with stable heart rate (HR), corresponding to heart rate deflection point (HRDP). Eight male volunteers, trained cyclists (23,2 + 4,4 years old; maximal oxygen consumption of 63,8 + 6,0 ml.kg-1.min-1 ) participated in this study. Seven from the eight volunteers which performed a modified Conconi test in cycloergometer, showed HRDP. One week later, the seven subjects performed an exercise during 45 minutes in a cycloergometer with a stable HR within a HR zone which corresponded to HRDP minus five heart beats per minute (bpm). All of the seven subjects were able to perform the exercise in the intensity prescribed during the 45 minutes. The lactate levels in minutes 5 and 15 were significantly different from 4 mmol/l. In the minutes 25, 35 e 45 of the exercise, the lactate levels were not different from 4 mmol/l. The results obtained in the present study indicate that the continuous exercise in the intensity prescribed by HR determined by the HRDP can be sustained for 45 minutes with blood lactate levels near to 4 mmol/l, except in the firsts minutes of exercise, which suggests a relationship between anaerobic threshold of 4 mmol/l and the HRDP determined by the Conconi test.
Keywords: heart rate; lactate; Conconi